Digital Taxation on Over-The-Top Services: A Comparative Study of Regulations in Indonesia and the ASEAN Region - Sugeng; Aidy, Widya Romsindah; Jr., Andre Cardenas (Universitas Airlangga, 2025)
Digital transformation has driven the rapid growth of Over-the-Top (OTT) services in the ASEAN region, including Indonesia, presenting new challenges for national tax systems. The digital and cross-border nature of the OTT business model, operating without the need for a physical presence (permanent establishment), has led to regulatory gaps in taxation, particularly in the collection of Value Added Tax (VAT) and Corporate Income Tax (CIT) for foreign OTT companies. This study aims to analyze digital tax policies for OTT services in Indonesia and compare them with those of ASEAN countries, including Singapore, Malaysia, Thailand, and Vietnam. The research uses a normative juridical method, employing both a statutory approach and a comparative approach. The data are sourced from national and international regulations related to digital taxation, academic journals, and policy studies from global organizations such as the Organisation for Economic Co-operation and Development (OECD) and G-20. The analysis compares OTT tax regulations across Indonesia and selected ASEAN countries to identify similarities, differences, and implementation challenges in digital tax policy. The findings indicate that The Association of Southeast Asian Nations (ASEAN) countries adopt diverse approaches to taxing OTT services, such as the Goods and Services Tax (GST) in Singapore, the Digital Servicce Tax (DST) in Malaysia, and Digital Income Tax Regimes (DITR) in Vietnam and Thailand. These measures reflect concerted efforts to enhance fiscal fairness, increase state revenue, and foster the sustainable growth of the digital economy. For Indonesia, it is recommended to strengthen its DST framework, implement technology-driven monitoring systems utilizing big data and Artificial Intelligence (AI), and align its digital taxation policies with international standards.